Regulatory Approaches and Strategies for Household Waste Pollution Management in the East River Flood Canal of Semarang City - Nirwana, Muhammad Alfaruq (Universitas Islam Negeri Walisongo Semarang, 2023)
This article explores regulations and strategies for managing the impact of household waste pollution in the East River Flood Canal of Semarang City. Water, crucial for human and environmental well-being, faces pollution challenges due to human activities. The study focuses on Semarang, where household waste pollution, often discarded along riverbanks, poses environmental threats. Primary data is collected through field interviews, complemented by secondary legal materials using socio-legal research methods. Regional Regulation No. 6 of 2012 addresses waste management in Semarang, aiming to empower residents in waste utilization and economic value creation. Law Number 32 of 2009 emphasizes collaborative efforts to address environmental challenges. Identified impacts of waste pollution include air and water pollution, contributing to flooding. A SWOT analysis suggests strategies such as enhancing stakeholder support, advocating the vision and mission for integrated waste management, establishing communication forums, leveraging ward roles in community counselling, and enhancing resource capacity to shift public perceptions and behaviours in waste management. This research aims to contribute to sustainable waste management practices and environmental preservation. Artikel ini mengeksplorasi regulasi dan strategi pengelolaan dampak pencemaran limbah rumah tangga di Banjir Kanal Sungai Timur Kota Semarang. Air, yang sangat penting bagi kesejahteraan manusia dan lingkungan, menghadapi tantangan polusi akibat aktivitas manusia. Studi ini berfokus di Semarang, dimana pencemaran limbah rumah tangga, yang sering dibuang di sepanjang tepi sungai, menimbulkan ancaman terhadap lingkungan. Data primer dikumpulkan melalui wawancara lapangan yang dilengkapi dengan bahan hukum sekunder dengan menggunakan metode penelitian sosio-legal. Peraturan Daerah Nomor 6 Tahun 2012 mengatur tentang pengelolaan sampah di Kota Semarang yang bertujuan untuk memberdayakan warga dalam pemanfaatan sampah dan penciptaan nilai ekonomi. Undang-Undang Nomor 32 Tahun 2009 menekankan upaya kolaboratif untuk mengatasi tantangan lingkungan hidup. Dampak pencemaran limbah yang teridentifikasi meliputi pencemaran udara dan air, yang berkontribusi terhadap banjir. Analisis SWOT menyarankan strategi seperti meningkatkan dukungan pemangku kepentingan, mendukung visi dan misi pengelolaan sampah terpadu, membentuk forum komunikasi, memanfaatkan peran lingkungan dalam konseling masyarakat, dan meningkatkan kapasitas sumber daya untuk mengubah persepsi dan perilaku masyarakat dalam pengelolaan sampah. Penelitian ini bertujuan untuk berkontribusi pada praktik pengelolaan sampah berkelanjutan dan pelestarian lingkungan.